Aplicaciones Pedagógicas del Refractómetro Digital en Procesos de Transformación Agroindustria. - Catota Ruiz, Gema Viviana (2022)
The present project had as a general objective the elaboration of a manual of pedagogical application and operation of the Digital Refractometer belonging to the laboratories of the Agroindustry Career of the Technical University of Cotopaxi. The digital refractometer is used to know the amount of soluble solids in liquids. This manual provides technicians, teachers and students with a reference for the correct operation of the refractometer. At the beginning, the technical characteristics of the instrument, measurement procedure and calibration are presented, also a control record is detailed. Then, a routine maintenance manual is elaborated, that includes the proper procedure for cleaning the prism to avoid possible damage and how often the battery should be changed. Subsequently, two practical demonstrations were conducted about the use of the Digital Refractometer, where in one of them the measurement of soluble solids was carried out, for this, two different brands of each orange-based product (juices, nectars and pulps) were used, the results obtained from the comparisons made between the juices were 13 and 9.9 °Brix, nectars is 7.1 and 6 .5°Brix and in the pulps it is 9.7 and 7.6°Brix, the same that fulfill with the ranges required in the NTE INEN 2 337:2008. In the practice that corresponds to the measurement of the alcoholic potential of beers of four different brands, the results obtained from the comparisons made were the following: Siembra 2.8%v/v alcoholic potential, Biela 3.3%v/v alcoholic potential, Pilsener 2.6%v/v alcoholic potential and Club 3.6%v/v alcoholic potential, to verify that the data obtained was real, it was compared with the NTE INEN 2262: 2013. Finally, the manual will include a technical sheet of the digital refractometer detailing its main characteristics.